EVALUASI PEMBELAJARAN BAHASA INDONESIA BERBASIS LITERASI DI SEKOLAH DASAR - Ananda, Rizki; Hidayati, Salmi; Suci Rahmadani, Indah; Raudhatul Jannah, Wilda; Adelya , Yaumi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Primary education is the first level of formal education in the Indonesian education system, intended for clhildren eged 6 to 12 years. The method used in this research is a literature study whith a qualitative approach, gethring information from various sources such as jpurnals and scientific articel. The results of the study indicate a lack of literacy among students ; therefore, educator also need to understand various methods of conducting evaluations to achieve better results, one of which is by utilizing digital technology.